Open education videos in the classroom: exploring the opportunities and barriers to the use of YouTube in teaching introductory sociology - Elaine Tan; Nick Pearce (Association for Learning Technology, 2011)
The use of open education resources has become more commonplace in classroom teaching and this has been an observable and growing trend. The accessibility of the same materials further reinforces the change in roles of the teacher, from gatekeeper of knowledge to learning facilitator. Our research question is that if a student has free and easy access to the same materials that are being used to teach them in class, how does this affect their perceptions when they are presented with this material in the classroom environment? What are their perceptions regarding the perceived value for money, efficacy and authority of the material? This research specifically investigated the use of open education videos in the classroom environment and their incorporation into an associated space in the virtual learning environment. The research questions of this investigation surrounded the practical, technical and pedagogical issues that arise from the incorporation of these resources within class and online course materials as well as exploring student perceptions about the use of this material in the class and online.